2018
DOI: 10.1126/science.aat4723
|View full text |Cite
|
Sign up to set email alerts
|

Slab2, a comprehensive subduction zone geometry model

Abstract: Subduction zones are home to the most seismically active faults on the planet. The shallow megathrust interfaces of subduction zones host Earth's largest earthquakes and are likely the only faults capable of magnitude 9+ ruptures. Despite these facts, our knowledge of subduction zone geometry-which likely plays a key role in determining the spatial extent and ultimately the size of subduction zone earthquakes-is incomplete. We calculated the three-dimensional geometries of all seismically active global subduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

45
1,182
4
18

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 995 publications
(1,348 citation statements)
references
References 39 publications
45
1,182
4
18
Order By: Relevance
“…For example, in the central Sunda arc values of H change by more than 100 km, over horizontal separations of less than 150 km (Pacey et al, ). We have shown that Mariana is another example of this variation, since H for active arc volcanoes, determined from the SLAB2 model (Hayes et al, ), ranges from 110 to 180 km across the arc. This entire range is apparent over short distances in the south, from Tracey to Esmerelda, where there can be no change in slab descent speed (Figures and S1).…”
Section: Discussionmentioning
confidence: 76%
“…For example, in the central Sunda arc values of H change by more than 100 km, over horizontal separations of less than 150 km (Pacey et al, ). We have shown that Mariana is another example of this variation, since H for active arc volcanoes, determined from the SLAB2 model (Hayes et al, ), ranges from 110 to 180 km across the arc. This entire range is apparent over short distances in the south, from Tracey to Esmerelda, where there can be no change in slab descent speed (Figures and S1).…”
Section: Discussionmentioning
confidence: 76%
“…In addition to the Moho, we also consider two crustal discontinuities modified from the CRUST1.0 model (Laske et al, ) and finally constructed a three‐layer crustal model (Figures S3 and S4). To date, several models for the geometry of the subducting Pacific slab beneath Alaska have been proposed (e.g., Gou, Zhao, et al, ; Hayes et al, ; Jadamec & Billen, ; J. Li et al, ; Zhao et al, ), but these slab models are different from each other, especially in the fore‐arc area of south‐central Alaska. In this study, we adopt the slab model produced by J. Li et al () in the starting model for the tomographic inversion, which was inferred from the Wadati‐Benioff zone seismicity located precisely using the double‐difference earthquake location method (Waldhauser & Ellsworth, ).…”
Section: Methodsmentioning
confidence: 99%
“…Geomorphological observations indicate spatially variable roughness of subducting seafloor at different subduction margins (Kopp, 2013; Lallemand et al, 2018; Ryan et al, 2009). Field and laboratory observations have also documented variations in other parameters, including plate convergence rate (DeMets et al, 2010), slab dip angle (Hayes et al, 2018), and subduction décollement strength (Ikari, 2019; Ikari & Kopf, 2017). Detailed regional studies suggest that some of these subduction zone parameters can even vary substantially over short distances along strike at a single margin, possibly leading to contrasting forearc features including megathrust locking state and slip behavior, wedge morphology and faulting style, and sediment consolidation state (e.g., [Sumatra] Dean et al, 2010; [Cascadia] Han et al, 2017; [Alaska] Li et al, 2018; [Hikurangi] Wallace et al, 2009).…”
Section: Methodsmentioning
confidence: 99%